Challenges and opportunities faced by social entrepreneurs in Sekhukhune District Municipality, Limpopo - Moipane, Phasha Pharane (University of the Witwatersrand, Johannesburg, 2023)
Background: Social entrepreneurship is increasingly recognised as a powerful means to address pressing societal issues. However, a substantial gap exists in the literature regarding the challenges and opportunities faced by social entrepreneurs in the Sekhukhune District Municipality (SDM) in Limpopo. This study aims to fill this gap by investigating the specific hurdles and prospects encountered by social entrepreneurs within this geographically isolated context. Significance: Social entrepreneurs play a pivotal role in mitigating socio-economic challenges and fostering community development. Their contributions are especially significant in underserved areas like the SDM. Population and Sample Framework: Data for this study was collected through interviews, articles, reports, and websites. Out of 50 social entrepreneurs approached, 26 accepted to be interviewed, constituting the study's sample. Method of Data Collection and Analysis: Qualitative research methods were employed to conduct interviews with the 26 social entrepreneurs operating in the SDM of Limpopo Province, South Africa. The data collected was analysed to uncover the challenges and opportunities faced by these social entrepreneurs. Highlights of Results: The study's findings underscore the substantial obstacles faced by social entrepreneurs in this region, which include insufficient funding, restricted access to networks, and inadequate training. These challenges hinder their project financing and sustainability efforts. Conclusions and Recommendations: This study recommends expanding local economic development and municipal procurement policies to provide interest-free grants to emerging entrepreneurs in the region. Furthermore, it suggests that social entrepreneurs can overcome some of these challenges by harnessing support from customers and leveraging tender opportunities provided by the SDM and other entities
A research report submitted in partial fulfillment of the requirements for the degree of Master of Business Administration to the Faculty of Commerce, Law, and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: Social Entrepreneurs; Funding; South Africa; Challenges; Opportunities; Policy Support; UCTD; SDG-8: Decent work and economic growth